A Grammar of Paraguayan Guarani - Estigarribia, Bruno (Grammars of World and Minority Languages, 2020)
The history of Guarani is a history of resilience. Paraguayan Guarani is a vibrant, modern language, mother tongue to millions of people in South America. It is the only indigenous language in the Americas spoken by a non-ethnically indigenous majority, and since 1992, it is also an official language of Paraguay alongside Spanish. This book provides the first comprehensive reference grammar of Modern Paraguayan Guarani written for an English-language audience. It is an accessible yet thorough and carefully substantiated description of the language's phonology, morphosyntax, and semantics. It also includes information about its centuries of documented history and its current sociolinguistic situation. Examples come from literary sources and film, scholastic grammars, online newspapers, blogs and other publications, publicly accessible social media data, and the author's own fieldwork. They are specifically chosen to reflect the diversity of uses of modern-day Guarani, with the aim of providing a realistic picture of the current state of the language in twenty-first century Paraguay. This book will benefit researchers and students of Guarani and Paraguay, such as linguists, anthropologists, ethnographers, sociologists, historians, or cultural studies and literature scholars. Typologically-oriented researchers and students of other Tupian and Amerindian languages will have reliable data for comparative purposes. Given the unique socio-historical profile of Guarani, researchers in fields such as language contact, bilingualism, code-switching, language planning, language education, and literacy will find this book a valuable reference resource.